Relationship Between Parenting Styles, Posyandu Visit Compliance, and Stunting in Toddlers: A Cross-Sectional Study - Kristianingrum, Anis Dwi; Maghfuroh, Lilis; Aisyah, Harnina Samantha (Universitas Muhammadiyah Semarang, 2026)
Stunting is a chronic growth disorder in children under five years old caused by prolonged malnutrition and inadequate nutritional intake. Several factors contribute to stunting, including poor parenting practices, low maternal education, limited family income, and irregular attendance at community health services such as Posyandu. This study aimed to analyze the relationship between parenting patterns and adherence to Posyandu visits with the incidence of stunting among children aged 12–59 months in Putatkumpul Village, Turi District, Lamongan Regency. This study employed a quantitative correlational design with a cross-sectional approach. The sample consisted of 127 parents with toddlers selected using simple random sampling. Data were collected using questionnaires assessing parenting patterns and adherence to Posyandu visits, while stunting status was determined using child growth charts. Data analysis was performed using the Spearman rho test in SPSS version 22.0 with a significance level of p < 0.05. The findings revealed that 14.5% of respondents with an authoritative parenting style had stunted children. Statistical analysis showed a significant relationship between parenting patterns and stunting incidence (p = 0.010; rs = 0.228), indicating a weak correlation. Furthermore, all respondents with high adherence to Posyandu visits had non-stunted children. A significant relationship was also found between adherence to Posyandu visits and stunting incidence (p = 0.009; rs = 0.230), indicating a weak correlation. Although parenting practices and Posyandu attendance are not direct causes of stunting, both contribute to early detection of growth problems and support optimal child nutrition. Therefore, health education regarding appropriate parenting and the importance of regular Posyandu visits is essential to improve stunting prevention efforts at the community level.